Action learning and action research : genres and approaches - Zuber-Skerritt, Ortrun; Wood, Lesley, 1957- (Emerald Publishing, 2019)
Action Learning and Action Research deepens understanding and contributes to new knowledge about the theory, practice and processes of Action Learning (AL) and Action Research. It clarifies what constitutes AL/AR in its many forms and what it is not.